Drug patents: the right policy for the wrong problem - Pasqualina Curcio Curcio (Social Medicine Publication Group, 2012)
Knowledge, according to economic theory, is a public good: it is non-exclusive, which means that the private sector, whose aim is to maximize profits, has no incentive to produce it since it can neither recover its investment costs nor make a profit. Since private industry cannot recover the cost of producing new knowledge they have no motivation to invest in research and development (R&D). Knowledge is also a non-rival good; the fact that a pharmaceutical company (public or private) uses and consumes a particular knowledge in the manufacture of a particular medication does not prevent other companies from also making use of the same knowledge to produce an identical product. The existence of public goods creates what economy theory calls "market failures." These are situations in which the market alone cannot efficiently allocate resources. When producers cannot force consumers to pay for the consumption of a good they cannot recover their production costs, much less maximize their profits (in the case of private producers). The resulting incomplete markets are a failure from the economic point-of-view. To overcome market failures, an external agent is required to intervene. In the case of public goods, the state must create public policies that reduce or eliminate market failures by supplementing the market through a guaranteed supply of these goods.